Correlation between NSTE-ACS risk scores with Syntax: can we predict coronary lesion complexity before angiography?. (3rd October 2022) - Maltes, S; Paiva, M S; Madeira, S; Teles, R C; Almeida, M S; Mendes, M
Abstract: Background and aim: Standard single antiplatelet regimen (SAPT) is currently recommended before invasive risk stratification in non-ST elevation acute coronary syndromes (NSTE-ACS). However, there are subsets in whom dual antiplatelet therapy (DAPT) may be more protective according to the coronary anatomy and revascularization strategy. We aimed to identify pre-procedural predictors of coronary artery complexity that may be helpful in selecting an individualized antiplatelet regimen. Methodology: Retrospective single-center study including patients with NSTE-ACS performing coronary angiography between January 2020 and July 2021. Clinical variables and classical NSTE-ACS risk scores (TIMI, GRACE and HEART) were captured and SYNTAX 1 score was calculated. Patients were divided into low (0–22), moderate (23–32) and high (≥33) SYNTAX score. Multivariate logistic regression analysis was performed to determine predictors of anatomical complexity (defined as significant left main disease [stenosis ≥50%] or SYNTAX ≥33). Results: A total of 448 patients were included (mean age 67±13 years; 74% males; 85% with NSTE-myocardial infarction). Overall, 350 (78%), 63 (14%) and 35 (8%) patients had a low, moderate or high-SYNTAX score, respectively. Thirty-one (7%) patients had significant left main disease. At multivariate analysis (adjusted for age, diabetes, renal function, GRACE and TIMI scores), the HEART score (hazard ratio 2.3, 95% confidence interval 1.5–3.3, p<0.001) predicted a high anatomical complexity. When performing ROC curve analysis, the HEART score had a high discriminative ability in identifying those with complex coronary anatomy (area under the curve 0.79, 95% CI 0.72–0.86, p<0.001) (Figure 1) – a score >7 showed a sensitivity of 76% and specificity of 75% in identifying such patients. Conclusion: In this cohort of NSTE-ACS patients, the HEART score was an independent predictors of complex coronary anatomies. These results suggest that those with high (>7) HEART score may merit from SAPT as opposed to DAPT, given the high probability of complex lesions amenable to CABG. Funding Acknowledgement: Type of funding sources: None.